Aluminophosphate LTA molecular sieve and its preparation method and application
Synthesis of aluminum phosphate LTA molecular sieve by sol-gel method with a single small molecule template agent has solved the problems of large consumables, high costs and serious environmental pollution in the prior art, and achieved the small particle size, large specific surface area and hydrothermal stability of the molecular sieve The effect improves the adsorption and separation performance of multi-component gases.
Patent Information
- Application Number
- CN202410931699.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-11
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-07-11
AI Technical Summary
The existing preparation methods of LTA molecular sieve are large in materials, high in cost, serious environmental pollution, and the prepared molecular sieve has a large particle size and low specific surface area, which is not conducive to adsorbing small molecular substances.
The aluminum phosphate LTA molecular sieve was synthesized by sol-gel method using a single small molecule template agent, which reduced the use of template agent and improved the characteristics of the molecular sieve with small particle size, large specific surface area and regular pore structure.
The prepared aluminum phosphate LTA molecular sieve has good hydrothermal stability and high adsorption capacity, and performs excellently in adsorption and separation of multi-component gases.
Smart Images

Figure CN118877908B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of molecular sieve porous materials, and in particular relates to an aluminum phosphate (LTA) molecular sieve and a preparation method and application thereof. Background Art
[0002] Small molecule separation technology mainly separates and purifies a large number of chemical mixtures produced in industrial fields such as chemical, petrochemical and pharmaceutical industries. The main means currently include: low temperature distillation, membrane separation, adsorption separation, etc. Among them, adsorption separation technology is a technology that uses the strong adsorption capacity of porous solid adsorbents to selectively adsorb substances on the solid surface to achieve the separation of multi-component mixed gases. The conventional process of adsorption separation is to pass the gas mixture through an adsorption column filled with adsorbents, and the weakly adsorbed gas components flow out first to obtain the product, and the strongly adsorbed gas components need to be desorbed to achieve the regeneration and reuse of the adsorbent. Common porous materials used for adsorption separation include: activated carbon, molecular sieves, porous alumina, metal organic framework materials, etc. Among them, molecular sieves have been widely used in the field of adsorption separation because of their wide sources, low cost, simple synthesis, uniform microporous structure, high specific surface area and good hydrothermal stability.
[0003] Molecular sieves are a type of porous solid material with ordered pores of molecular size, mainly divided into silicates and aluminosilicates. The ordered pore structure makes it have excellent performance in adsorption separation, and its acidity can be changed by adjusting the silicon-aluminum ratio; high specific surface area, uniform pore size distribution; simple synthesis steps, low-cost and easy-to-obtain templates; good hydrothermal stability and chemical stability, etc., make it stand out among many adsorbent materials. The aluminum phosphate molecular sieve with LTA (International Molecular Sieve Association designated code) topological structure belongs to the cubic crystal system, has an 8-ring pore size and a large α cage, a three-dimensional pore structure, and a pore size of 0.41nm. Due to its unique pore size structure, it can be used as a good adsorbent material.
[0004] Under normal circumstances, LTA molecular sieves are prepared by using a variety of structure-directing methods under hydrothermal conditions. It is currently known that LTA molecular sieves are prepared by using a variety of structure-directing agents in coordination under hydrothermal conditions. For example, a mixture of tetramethylammonium hydroxide (TMAOH-5H2O, 97%), hydrofluoric acid (48%), tetraethyl silicate (TEOS, 98%), and aluminum hydroxide (Al(OH)3) is mixed in the presence of an imidazole-based (such as 1,2-dimethylimidazole, 1,2-dimethyl-3-(3-methylbenzyl)imidazole, etc.) organic structure-directing agent, and then the resulting mixture is heated at 80°C. The mixed product is then charged into a reactor and heated at 175°C, 60rpm, under dynamic conditions for the required time. The product is washed with deionized water, dried at room temperature overnight, and calcined in air at 600°C for 8h to obtain LTA molecular sieves. This method uses two templates to jointly guide the LTA aluminum phosphate molecular sieve. Compared with the present invention, it has large consumables, high costs, low environmental friendliness, and large molecular sieve particle size and small specific surface area, which is not conducive to mass transfer and gas adsorption.
[0005] At present, most LTA molecular sieves are produced by the traditional hydrothermal method using the synergistic action of two or more templates, such as Kryptofix 222, ternary organic templates, etc. The existing method consumes a lot of materials, is costly, and causes serious environmental pollution. In addition, the prepared molecular sieves have a large particle size and a low specific surface area, which is not conducive to the adsorption of small molecules. Summary of the invention
[0006] In order to solve the above technical problems, the present invention proposes an aluminum phosphate LTA molecular sieve and its preparation method and application, and adopts a single small molecule reagent as a template agent. The prepared molecular sieve has a small particle size, a large specific surface area, a regular pore structure, and good hydrothermal stability, and has broad prospects in the adsorption and separation of multi-component gases.
[0007] To achieve the above object, the present invention provides a method for preparing aluminum phosphate LTA molecular sieve, comprising the following steps:
[0008] (1) deionized water, aluminum source, phosphoric acid solution and HF solution are mixed and stirred to obtain a premixed solution;
[0009] (2) adding propylene oxide to the premixed solution of step (1) under ice bath stirring to obtain a hydrogel;
[0010] (3) drying and grinding the hydrogel in step (2) to obtain aluminum phosphate xerogel powder;
[0011] (4) mixing the aluminum phosphate dry gel powder described in step (3) with water, adding a template agent dropwise, stirring for a second time, and drying for a first time to obtain an aluminum phosphate precursor;
[0012] (5) The aluminum phosphate precursor described in step (4) is crystallized, sonicated, washed with water three times, subjected to a second drying treatment, and calcined to obtain an aluminum phosphate LTA molecular sieve.
[0013] Preferably, the aluminum source in step (1) is one of crystalline aluminum chloride, pseudo-boehmite and aluminum isopropoxide; the phosphoric acid solution in step (1) uses water as solvent, and the concentration of the phosphoric acid solution is 70 to 99 wt %; the HF solution in step (1) uses water as solvent, and the concentration of the HF solution is 30 to 70 wt %.
[0014] Preferably, the premixed solution in step (1) further comprises one of heteroatoms Fe, Co, Mg, Ni, Si or Cu and an ethanol solution; the ethanol solution uses water as a solvent, and the concentration of the ethanol solution is 75 to 99 wt%.
[0015] Preferably, in step (1), the temperature of the first stirring is 15 to 30° C., the time of the first stirring is 0.5 to 4 h, and the speed of the first stirring is 50 to 100 r / min; in step (2), the temperature of the ice bath stirring is -5 to 5° C., the time of the ice bath stirring is 0.1 to 2 h, and the speed of the ice bath stirring is 50 to 100 r / min.
[0016] Preferably, the molar ratio of Al2O3:P2O5:HF:PO:H2O in the hydrogel in step (2) is 0.1-1.0:0.1-5.0:0.1-2.0:1.0-50:20.0-1000 or the molar ratio of M:Al2O3:P2O5:HF:PO:H2O is 0.001-2.0:1.0:0.2-5.0:0.001-2.0:1.0-50:20-1000, wherein M represents one of the heteroatoms Fe, Co, Mg, Ni, Si or Cu.
[0017] Preferably, the drying temperature in step (3) is 80 to 120° C., and the drying time is 1 to 24 hours.
[0018] Preferably, the template agent in step (4) is one of tetramethylammonium hydroxide, di-n-propylamine, 1-ethyl-3-methylimidazolium bromide or 1-butyl-3-methylimidazolium bromide; the template agent is added at a rate of 1 to 50 drops / min in step (4); the second stirring time in step (4) is 2 to 6 hours, and the second stirring speed is 50 to 100 r / min; the temperature of the first drying treatment in step (4) is 60 to 100° C., and the first drying treatment time is 0.5 to 10 hours.
[0019] Preferably, the crystallization temperature in step (5) is 150-200°C, and the crystallization time is 1-72h; the ultrasound power in step (5) is 50-300W, and the ultrasound time is 5-30min; the second drying temperature in step (5) is 80-120°C, and the second drying time is 1-12h; the calcination temperature in step (5) is 450-600°C, and the calcination time is 4-16h.
[0020] The present invention also provides the aluminum phosphate LTA molecular sieve prepared by the preparation method.
[0021] The present invention also provides the use of the aluminum phosphate LTA molecular sieve or the aluminum phosphate LTA molecular sieve prepared by the preparation method in the adsorption separation of multi-component gases.
[0022] Compared with the prior art, the present invention has the following advantages and technical effects:
[0023] 1) The present invention provides a method for synthesizing aluminum phosphate LTA molecular sieves by using a sol-gel method and a single small molecule template. In the prior art, most molecular sieves with an LTA topological structure can only be synthesized by using two or more templates in synergy, and the obtained aluminum phosphate LTA molecular sieve has a large particle size, which is not conducive to the adsorption and separation of gases. The LTA molecular sieve synthesized by the present invention breaks the disadvantage of the previous large particle size. The synthesized molecular sieve has a small particle size, a unique 8-membered ring pore size, a large specific surface area, and good hydrothermal stability. Even at higher temperatures and lower pressures, it still has a higher adsorption capacity, and has a brilliant performance in the adsorption and separation of multi-component gases;
[0024] 2) The aluminum phosphate LTA molecular sieve prepared by the present invention introduces heteroatoms into the LTA molecular sieve framework, which gives the molecular sieve new active sites, improves the acidity and redox properties of the molecular sieve, and also has broad prospects in the adsorption and separation of multi-component gases. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 XRD spectrum of the aluminum phosphate LTA molecular sieve prepared in Example 1 of the present invention;
[0027] Figure 2 This is a SEM image of the aluminum phosphate LTA molecular sieve prepared in Example 1 of the present invention, with a scale of 2 μm;
[0028] Figure 3 The single component adsorption isotherms of the aluminum phosphate LTA molecular sieve prepared in Example 1 of the present invention for N2, CO2, and CH4 at 298K;
[0029] Figure 4 The ideal adsorption selectivity curve of the aluminum phosphate LTA molecular sieve prepared in Example 1 of the present invention for CO2 / N2;
[0030] Figure 5 The ideal adsorption selectivity curve of the aluminum phosphate LTA molecular sieve prepared in Example 1 of the present invention for CO2 / CH4;
[0031] Figure 6 This is the ideal adsorption selectivity curve of the aluminum phosphate LTA molecular sieve prepared in Example 1 of the present invention for CH4 / N2. DETAILED DESCRIPTION
[0032] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0033] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0034] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0035] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0036] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0037] Example 1
[0038] (1) In a 50 mL beaker, 9 g of deionized water and 0.701 g of pseudo-boehmite were added in sequence, and then 1.2 g of H3PO4 solution (85 wt%) and 0.2 g of HF solution (40 wt%) were slowly added dropwise at a rate of 10 drops / min, and the mixture was stirred at 500 r / min and 23° C. for 2 h to obtain a premixed solution;
[0039] (2) Under 0°C ice bath conditions, 6 mL of propylene oxide was slowly added to the premixed solution at a rate of 12 drops / min, and the mixture was stirred at 200 r / min in a 0°C ice bath for 1 h until the solution became a gel state to obtain a hydrogel. The molar ratio of Al2O3:P2O5:HF:PO (propylene oxide):H2O in the hydrogel was 1.0:1.0:0.8:14.3:100;
[0040] (3) drying the hydrogel (putting it in an oven at 80°C for aging for 2 h, transferring it to a culture dish after aging, and drying it in an oven at 100°C for 2 h), and grinding it to obtain aluminum phosphate xerogel powder;
[0041] (4) Take another 50 mL beaker, add aluminum phosphate dry gel powder and 18 g deionized water, slowly add 2.8 g di-n-propylamine (DPA) at 10 drops / min, stir for 4 h at 500 r / min, and dry in an oven at 100 ° C for 2 h to obtain an aluminum phosphate precursor;
[0042] (5) The aluminum phosphate precursor was placed in a reactor, crystallized at 180° C. for 24 h, ultrasonically treated at an ultrasonic power of 100 W for 15 min, washed with water three times, subjected to a second drying treatment at 100° C. for 6 h, and calcined at 500° C. in an air atmosphere for 8 h to obtain an aluminum phosphate LTA molecular sieve.
[0043] The ideal adsorption solution theory (IAST) was used to further evaluate the separation selectivity of the aluminum phosphate LTA molecular sieve prepared in Example 1 for multi-component gases at 298 K. The binary Langmuir-Freundlich equation was used to fit the single-component adsorption isotherm.
[0044] The results are as follows Figure 1 to Figure 6 As shown, Figure 1It can be seen from the XRD spectrum that the aluminum phosphate LTA molecular sieve prepared in Example 1 has strong diffraction peaks at 2θ=7.41°, 10.49°, 12.85°, 22.38° and 24.78°, and compared with the standard card, it is found that the aluminum phosphate LTA molecular sieve prepared in Example 1 has a typical LTA topological structure. At the same time, the XRD spectrum of the aluminum phosphate LTA molecular sieve prepared in Example 1 has a smooth baseline, a high diffraction peak intensity and no obvious impurity peaks, indicating that it has high crystallinity and purity.
[0045] like Figure 2 The SEM image of the aluminum phosphate LTA molecular sieve prepared in Example 1 is shown in FIG. 1 . The LTA crystals present a typical cubic structure, and most of the particle sizes are between 0.5 and 1 μm. The single-component adsorption isotherms of the aluminum phosphate LTA molecular sieve prepared in Example 1 for CO2, CH4 and N2 at 298K and 0 to 100KPa are shown in FIG. Figure 3 As shown, the prepared aluminum phosphate LTA molecular sieve has a much higher adsorption capacity for CO2 than CH4 and N2. On the one hand, this is because the molecular size of CO2 is smaller than that of CH4 and N2 (CO2: 0.33nm, CH4: 0.38nm, N2: 0.36nm). On the other hand, the strong quadrupole moment of CO2 has sufficient interaction ability to induce the molecular sieve pore cations to temporarily and reversibly deviate from the pore center, thereby allowing the CO2 molecules to pass through the molecular sieve.
[0046] The ideal adsorption solution theory (IAST) was then used to further evaluate the separation selectivity of the prepared aluminum phosphate LTA molecular sieve for multi-component gases at 298K. The binary Langmuir-Freundlich equation was used to fit the single-component adsorption isotherm. The results are shown in Figures 4 to 6 As shown, it can be seen that the aluminum phosphate LTA molecular sieve sample prepared in Example 1 has an ideal selectivity for CO2 / N2, CO2 / CH4, and CH4 / N2. Under low pressure (less than 20Kpa), the selectivity gradually decreases, and as the pressure increases, the selectivity gradually increases. Finally, at 100KPa, the ideal selectivities reach 36.5, 16.2, and 4.2, respectively, which are all higher than the literature values, indicating that the aluminum phosphate LTA molecular sieve sample prepared in Example 1 has good multi-component gas separation performance.
[0047] Example 2
[0048] (1) In a 50 mL beaker, 9 g of deionized water and 1.402 g of pseudo-boehmite were added in sequence, and then 1.5 g of H3PO4 solution (85 wt%) and 0.3 g of HF solution (40 wt%) were slowly added dropwise at a rate of 5 drops / min, and stirred for 2 h at 600 r / min and 25° C. to obtain a premixed solution;
[0049] (2) Under 0°C ice bath conditions, 4.0 mL of propylene oxide was slowly added to the premixed solution at a rate of 12 drops / min, and stirred at 400 r / min in a 0°C ice bath for 1 h until the solution became a gel state to obtain a hydrogel. The molar ratio of Al2O3:P2O5:HF:PO (propylene oxide):H2O in the hydrogel was 1.0:1.25:1.2:11.4:100;
[0050] (3) drying the hydrogel (putting it in an oven at 80°C for aging for 2 h, transferring it to a culture dish after aging, and drying it in an oven at 100°C for 2 h), and grinding it to obtain aluminum phosphate xerogel powder;
[0051] (4) Take another 50 mL beaker, add aluminum phosphate dry gel powder and 18 g deionized water, slowly add 2.8 g di-n-propylamine (DPA) at 10 drops / min, rotate at 400 r / min, stir for 4 h, and dry in an oven at 100 ° C for 5 h to obtain an aluminum phosphate precursor;
[0052] (5) The aluminum phosphate precursor was placed in a reactor, crystallized at 180° C. for 24 h, ultrasonicated at 200 W for 10 min, washed with water three times, dried at 100° C. for 6 h, and calcined at 500° C. in air for 8 h to obtain aluminum phosphate LTA molecular sieve.
[0053] Example 3
[0054] (1) In a 50 mL beaker, 18 g of deionized water and 0.701 g of pseudo-boehmite were added in sequence, and then 1.2 g of H3PO4 solution (85 wt%) and 0.2 g of HF solution (40 wt%) were slowly added dropwise at a rate of 15 drops / min, and the mixture was stirred at 300 r / min and 25° C. for 2 h to obtain a premixed solution;
[0055] (2) Under 0°C ice bath conditions, 6 mL of propylene oxide was slowly added to the premixed solution at a rate of 12 drops / min, and stirred at 300 r / min in a 0°C ice bath for 1 h until the solution became a gel state to obtain a hydrogel. The molar ratio of Al2O3:P2O5:HF:PO (propylene oxide):H2O in the hydrogel was 1.0:1.0:0.8:16:200;
[0056] (3) drying the hydrogel (putting it in an oven at 80°C for aging for 2 h, transferring it to a culture dish after aging, and drying it in an oven at 100°C for 2 h), and grinding it to obtain aluminum phosphate xerogel powder;
[0057] (4) Take another 50 mL beaker, add aluminum phosphate dry gel powder and 18 g deionized water, slowly add 3 g di-n-propylamine (DPA) at 12 drops / min, stir for 4 h at 400 r / min, and dry in an oven at 100 ° C for 4 h to obtain an aluminum phosphate precursor;
[0058] (5) The aluminum phosphate precursor was placed in a reactor, crystallized at 200° C. for 12 h, ultrasonicated at 50 W for 20 min, washed with water three times, dried at 100° C. for 6 h, and calcined at 500° C. in air for 8 h to obtain aluminum phosphate LTA molecular sieve.
[0059] Example 4
[0060] (1) In a 50 mL beaker, 18 g of deionized water and 1.402 g of pseudo-boehmite were added in sequence, and then 1.2 g of H3PO4 solution (85 wt%) and 0.3 g of HF solution (40 wt%) were slowly added dropwise at a rate of 10 drops / min, and the mixture was stirred at 500 r / min and 30° C. for 2 h to obtain a premixed solution;
[0061] (2) Under 0°C ice bath conditions, 4.5 mL of propylene oxide was slowly added to the premixed solution at a rate of 12 drops / min, and the mixture was stirred at 400 r / min in a 0°C ice bath for 1 h until the solution became a gel state to obtain a hydrogel. The molar ratio of Al2O3:P2O5:HF:PO (propylene oxide):H2O in the hydrogel was 1.0:0.5:0.6:6.4:100;
[0062] (3) The hydrogel was dried (placed in an oven at 80°C for aging for 2 h, and after aging, transferred to a culture dish and dried in an oven at 100°C for 2 h), and ground to obtain aluminum phosphate xerogel powder;
[0063] (4) Take another 50 mL beaker, add aluminum phosphate dry gel powder and 18 g deionized water, slowly add 1.8 g di-n-propylamine (DPA) at 8 drops / min, stir for a second time at 500 r / min for 4 h, and dry in an oven at 100 ° C for 4 h to obtain an aluminum phosphate precursor;
[0064] (5) The aluminum phosphate precursor was placed in a reactor, crystallized at 160° C. for 8 h, ultrasonicated at 100 W for 5 min, washed with water 3 times, dried at 100° C. for 6 h, and calcined at 500° C. in air for 8 h to obtain aluminum phosphate LTA molecular sieve.
[0065] Example 5
[0066] (1) In a 50 mL beaker, 18 g of deionized water, 0.701 g of pseudo-boehmite, and 0.354 g of cobalt acetate were added in sequence, and then 1.2 g of H3PO4 solution (85 wt%) and 0.2 g of HF solution (40 wt%) were slowly added dropwise at a rate of 15 drops / min, and the mixture was stirred at 300 r / min and 30° C. for 2 h to obtain a premixed solution;
[0067] (2) Under 0°C ice bath conditions, 6 mL of propylene oxide was slowly added dropwise at 12 drops / min to the premixed solution, and the mixture was stirred at 450 r / min in a 0°C ice bath for 1 h until the solution became a gel state to obtain a hydrogel. The molar ratio of Co2O3:Al2O3:P2O5:HF:PO (propylene oxide):H2O in the hydrogel was 0.20:1.0:1.0:0.8:17.2:200;
[0068] (3) The hydrogel was dried (placed in an oven at 80°C for aging for 2 h, and after aging, transferred to a culture dish and dried in an oven at 100°C for 2 h), and ground to obtain cobalt aluminum phosphate dry gel powder;
[0069] (4) Take another 50 mL beaker, add cobalt aluminum phosphate dry gel powder and 18 g deionized water, slowly add 2.0 g di-n-propylamine (DPA) at 20 drops / min, stir for a second time at 500 r / min for 4 h, and dry in an oven at 100 ° C for 4 h to obtain a cobalt aluminum phosphate precursor;
[0070] (5) The cobalt aluminum phosphate precursor was placed in a reactor, crystallized at 170° C. for 12 h, ultrasonicated at 100 W for 20 min, washed with water three times, dried at 100° C. for 6 h, and calcined at 500° C. in air for 12 h to obtain the cobalt aluminum phosphate LTA molecular sieve.
[0071] Example 6
[0072] (1) In a 50 mL beaker, 9 g of deionized water, 0.701 g of pseudo-boehmite, and 0.527 g of cobalt acetate were added in sequence, and then 2.4 g of H3PO4 solution (85 wt%) and 0.2 g of HF solution (40 wt%) were slowly added dropwise at a rate of 10 drops / min, and the mixture was stirred at 500 r / min and 30° C. for 2 h to obtain a premixed solution;
[0073] (2) Under 0°C ice bath conditions, 6 mL of propylene oxide was slowly added to the premixed solution at a rate of 20 drops / min, and the mixture was stirred at 300 r / min in a 0°C ice bath for 1 h until the solution became a gel state to obtain a hydrogel. The molar ratio of Co2O3:Al2O3:P2O5:HF:PO (propylene oxide):H2O in the hydrogel was 0.30:1.0:2.0:0.8:17.2:100;
[0074] (3) The hydrogel was dried (placed in an oven at 80°C for aging for 2 h, and after aging, transferred to a culture dish and dried in an oven at 120°C for 2 h), and ground to obtain cobalt aluminum phosphate dry gel powder;
[0075] (4) Take another 50 mL beaker, add cobalt aluminum phosphate dry gel powder and 10 g deionized water, slowly add 3.5 g di-n-propylamine (DPA) at 20 drops / min, stir for 4 h at 400 r / min, and dry in an oven at 100 ° C for 6 h to obtain a cobalt aluminum phosphate precursor;
[0076] (5) The cobalt aluminum phosphate precursor was placed in a reactor, crystallized at 150° C. for 24 h, ultrasonically treated at an ultrasonic power of 150 W for 10 min, washed with water three times, dried at 120° C. for a second time for 6 h, and calcined at 550° C. in an air atmosphere for 8 h to obtain the cobalt aluminum phosphate LTA molecular sieve.
[0077] Example 7
[0078] (1) In a 50 mL beaker, 9 g of deionized water, 10 g of anhydrous ethanol, 0.701 g of pseudo-boehmite, and 0.416 g of ethyl orthosilicate were added in sequence, and then 1.2 g of H3PO4 solution (85 wt%) and 0.3 g of HF solution (40 wt%) were slowly added dropwise at a rate of 10 drops / min, and the mixture was stirred at 300 r / min and 30° C. for 2 h to obtain a premixed solution;
[0079] (2) Under 0°C ice bath conditions, 4 mL of propylene oxide was slowly added dropwise at a rate of 15 drops / min to the premixed solution, and the mixture was stirred at 300 r / min in a 0°C ice bath for 1 h until the solution became a gel state to obtain a hydrogel. The molar ratio of SiO2:Al2O3:P2O5:HF:PO (propylene oxide):H2O in the hydrogel was 0.20:1.0:1.0:1.2:11.5:100;
[0080] (3) drying the hydrogel (putting it in an oven at 80°C for aging for 2 hours, transferring it to a culture dish after aging, and drying it in an oven at 100°C for 4 hours), and grinding it to obtain aluminosilicophosphate dry gel powder;
[0081] (4) Take another 50 mL beaker, add the aluminum silicophosphate dry gel powder and 18 g of deionized water, slowly add 2.5 g of di-n-propylamine (DPA) at 20 drops / min, stir for 4 h at 200 r / min, and dry in an oven at 100 ° C for 6 h to obtain an aluminum silicophosphate precursor;
[0082] (5) The silicoaluminophosphate precursor was placed in a reactor, crystallized at 180° C. for 18 h, ultrasonicated at 150 W for 25 min, washed with water three times, dried at 100° C. for 6 h, and calcined at 550° C. in air for 10 h to obtain a silicoaluminophosphate LTA molecular sieve.
[0083] Example 8
[0084] (1) In a 50 mL beaker, 9 g of deionized water, 10 g of anhydrous ethanol, 0.701 g of pseudo-boehmite, and 0.284 g of magnesium acetate tetrahydrate were added in sequence, and then 1.2 g of H3PO4 solution (85 wt%) and 0.25 g of HF solution (40 wt%) were slowly added dropwise at a rate of 15 drops / min, and the mixture was stirred at 500 r / min and 30° C. for 2 h to obtain a premixed solution;
[0085] (2) Under 0°C ice bath conditions, 5 mL of propylene oxide was slowly added dropwise at a rate of 10 drops / min to the premixed solution, and the mixture was stirred at 300 r / min in a 0°C ice bath for 1 h until the solution became a gel state to obtain a hydrogel, wherein the molar ratio of MgO:Al2O3:P2O5:HF:PO (propylene oxide):H2O in the hydrogel was 0.10:1.0:1.0:1.0:14.3:100;
[0086] (3) The hydrogel was dried (placed in an oven at 80°C for aging for 2 h, and after aging, transferred to a culture dish and dried in an oven at 120°C for 2 h), and ground to obtain magnesium aluminum phosphate dry gel powder;
[0087] (4) Take another 50 mL beaker, add magnesium aluminum phosphate dry gel powder and 18 g deionized water, slowly add 1.6 g di-n-propylamine (DPA) at 15 drops / min, stir for 4 h at 450 r / min, and dry in an oven at 100 ° C for 6 h to obtain a magnesium aluminum phosphate precursor;
[0088] (5) The magnesium aluminum phosphate precursor was placed in a reactor, crystallized at 190° C. for 6 h, ultrasonicated at 300 W for 5 min, washed with water 3 times, dried at 100° C. for 6 h, and calcined at 500° C. in an air atmosphere for 8 h to obtain a magnesium aluminum phosphate LTA molecular sieve.
[0089] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing aluminum phosphate LTA molecular sieve, characterized in that: The following steps are involved: (1) deionized water, aluminum source, phosphoric acid solution and HF solution are mixed and stirred to obtain a premixed solution; (2) adding propylene oxide to the premixed solution of step (1) under ice bath stirring to obtain a hydrogel; (3) drying and grinding the hydrogel in step (2) to obtain aluminum phosphate xerogel powder; (4) mixing the aluminum phosphate dry gel powder described in step (3) with water, adding a template agent dropwise, stirring for a second time, and drying for a first time to obtain an aluminum phosphate precursor; (5) The aluminum phosphate precursor of step (4) is crystallized, ultrasonicated, washed with water three times, dried for a second time, and calcined to obtain aluminum phosphate LTA molecular sieve; The molar ratio of Al2O3:P2O5:HF:PO:H2O in the hydrogel in step (2) is 0.1-1.0:0.1-5.0:0.1-2.0:1.0-50:20.0-1000; The template agent in step (4) is one of tetramethylammonium hydroxide, di-n-propylamine, 1-ethyl-3-methylimidazolium bromide or 1-butyl-3-methylimidazolium bromide.
2. The preparation method according to claim 1, characterized in that: The aluminum source in step (1) is one of crystalline aluminum chloride, pseudo-boehmite and aluminum isopropoxide; the phosphoric acid solution in step (1) uses water as solvent, and the concentration of the phosphoric acid solution is 70-99wt%; the HF solution in step (1) uses water as solvent, and the concentration of the HF solution is 30-70wt%.
3. The preparation method according to claim 1, characterized in that: The premixed solution in step (1) further comprises one of the heteroatoms Fe, Co, Mg, Ni, Si or Cu and an ethanol solution; the ethanol solution uses water as a solvent, and the concentration of the ethanol solution is 75 to 99 wt%.
4. The preparation method according to claim 1, characterized in that: In step (1), the temperature of the first stirring is 15 to 30° C., the time of the first stirring is 0.5 to 4 h, and the speed of the first stirring is 50 to 100 r / min; in step (2), the temperature of the ice bath stirring is -5 to 5° C., the time of the ice bath stirring is 0.1 to 2 h, and the speed of the ice bath stirring is 50 to 100 r / min.
5. The preparation method according to claim 1 or 3, characterized in that: The molar ratio of Al2O3:P2O5:HF:PO:H2O in the hydrogel in step (2) is 0.1-1.0:0.1-5.0:0.1-2.0:1.0-50:20.0-1000 or the molar ratio of M:Al2O3:P2O5:HF:PO:H2O is 0.001-2.0:1.0:0.2-5.0:0.001-2.0:1.0-50:20-1000, wherein M represents one of the heteroatoms Fe, Co, Mg, Ni, Si or Cu.
6. The preparation method according to claim 1, characterized in that: The drying temperature in step (3) is 80 to 120° C., and the drying time is 1 to 24 hours.
7. The preparation method according to claim 1, characterized in that: The template agent is added at a rate of 1 to 50 drops / min in step (4); the second stirring time in step (4) is 2 to 6 hours, and the second stirring speed is 50 to 100 r / min; the first drying treatment temperature in step (4) is 60 to 100° C., and the first drying treatment time is 0.5 to 10 hours.
8. The preparation method according to claim 1, characterized in that: The crystallization temperature in step (5) is 150-200°C, and the crystallization time is 1-72h; the ultrasound power in step (5) is 50-300W, and the ultrasound time is 5-30min; the second drying temperature in step (5) is 80-120°C, and the second drying time is 1-12h; the calcination temperature in step (5) is 450-600°C, and the calcination time is 4-16h.
9. Aluminophosphate LTA molecular sieve prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the aluminum phosphate LTA molecular sieve as claimed in claim 9 or the aluminum phosphate LTA molecular sieve prepared by the preparation method according to any one of claims 1 to 8 in the adsorption separation of multi-component gases.
Citation Information
Patent Citations
Rapid hydrothermal-synthesized H-LTA-type molecular sieve and preparation method and application thereof
CN109422275A
Low-silicon aluminum phosphate-based CHA molecular sieve with triclinic system as well as preparation method and application thereof
CN112573532A